2020
DOI: 10.1111/pim.12702
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma haematobium infection modulates Plasmodium falciparum parasite density and antimalarial antibody responses

Abstract: Aims Schistosomiasis and malaria are endemic in sub‐Saharan Africa where Schistosoma haematobium (Sh) and Plasmodium falciparum (Pf) coinfections are thus frequent. We explored the effect of Sh infection on antibody responses directed to Pf merozoite antigens and on malaria susceptibility in Beninese children. Methods and results A total of 268 children were followed during a malaria transmission season. Detection of Pf infection was performed by microscopy and rapid diagnostic tests. Sh infection was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 44 publications
3
13
2
Order By: Relevance
“…It should be noted that S . haematobium infection had no significant effect on the antibody responses directed to either MSP3 or GLURP, the two antigens combined in GMZ2, in contrast to the findings of a recent study [ 44 ], although the level of anti-GLURP IgG concentration was indeed higher in S . haematobium infected compared to uninfected individuals, but this difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It should be noted that S . haematobium infection had no significant effect on the antibody responses directed to either MSP3 or GLURP, the two antigens combined in GMZ2, in contrast to the findings of a recent study [ 44 ], although the level of anti-GLURP IgG concentration was indeed higher in S . haematobium infected compared to uninfected individuals, but this difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, S. haematobium could augment antibody production by influencing the biological environment through enhanced IL-4 production [6], favoring antimalarial antibody production [43]. It should be noted that S. haematobium infection had no significant effect on the antibody responses directed to either MSP3 or GLURP, the two antigens combined in GMZ2, in contrast to the findings of a recent study [44], although the level of anti-GLURP IgG concentration was indeed higher in S. haematobium infected compared to uninfected individuals, PLOS NEGLECTED TROPICAL DISEASES but this difference was not statistically significant. It is well known that MSP3 constitutes a less immunogenic component of GMZ2 [24,25], possibly explaining this observation.…”
Section: Discussioncontrasting
confidence: 59%
“…On the contrary, we found that antigen-specific IgG and total IgE responses were higher in the coexposure/coinfection group compared to the single exposure/infection groups. For P. falciparum , this is consistent with previous studies that reported increased P. falciparum -specific IgG1, IgG2, and IgG3 responses in coinfection with Schistosoma haematobium ( 40 , 41 ). In contrast, other studies have reported a detrimental effect of coinfection with helminths in the humoral response to malaria with a reduction in P. falciparum -specific IgG ( 42 ), IgG1 and IgG3 ( 43 , 44 ), and an increase in the non-cytophilic IgG4 ( 43 ).…”
Section: Discussionsupporting
confidence: 92%
“…Thirdly, there was a trend for higher P. falciparum burden in the coexposure/coinfection group compared to the P. falciparum single exposure/infection group in children, which is consistent with other reports for P. falciparum and P. vivax (Easton et al, 2020), but contrary to others (Amoani et al, 2019;Tokplonou et al, 2020). The only significant association for helminths with regards to parasite burden was for T. trichiura, where having been exposed to or currently infected with P. falciparum seemed to have a protective effect.…”
Section: Discussionsupporting
confidence: 90%
“…On the contrary, we found that antigen-specific IgG and total IgE responses were higher in the coexposure/coinfection group compared to the single exposure/infection groups. For P. falciparum, this is consistent with previous studies that reported increased P. falciparum-specific IgG1, IgG2 and IgG3 responses in coinfection with S. haematobium (Diallo et al, 2010;Tokplonou et al, 2020). In contrast, other studies have reported a detrimental effect of coinfection with helminths in the humoral response to malaria with a reduction in P. falciparum-specific IgG (Ateba-Ngoa et al, 2016), IgG1 and IgG3 (Courtin et al, 2011;Roussilhon et al, 2010), and an increase in the non-cytophilic IgG4 (Roussilhon et al, 2010).…”
Section: Discussionsupporting
confidence: 90%